2016
DOI: 10.1002/adma.201602958
|View full text |Cite
|
Sign up to set email alerts
|

3D Graphitic Foams Derived from Chloroaluminate Anion Intercalation for Ultrafast Aluminum‐Ion Battery

Abstract: A 3D graphitic foam vertically aligned graphitic structure and a low density of defects is derived through chloroaluminate anion intercalation of graphite followed by thermal expansion and electrochemical hydrogen evolution. Such aligned graphitic structure affords excellent Al-ion battery characteristics with a discharge capacity of ≈60 mA h g under a high charge and discharge current density of 12 000 mA g over ≈4000 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
217
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 318 publications
(230 citation statements)
references
References 16 publications
5
217
0
8
Order By: Relevance
“…Furthermore, the development of these batteries based on nonflammable electrolytes of low toxicity is critical for minimizing safety hazard and environmental impact. Recently, our group developed a secondary Al battery system based on the reversible deposition/stripping of aluminum at the Al negative electrode and reversible intercalation/deintercalation of chloroaluminate anions at the graphite positive electrode in a nonflammable 1-ethyl-3-methylimidazolium chloroaluminate (EMIC-AlCl 3 ) IL electrolyte (7,8). A ratio of AlCl 3 /EMIC = 1.3 by mole was used such that Al 2 Cl 7 − was present in the (acidic) electrolyte to facilitate aluminum deposition (9).…”
mentioning
confidence: 99%
“…Furthermore, the development of these batteries based on nonflammable electrolytes of low toxicity is critical for minimizing safety hazard and environmental impact. Recently, our group developed a secondary Al battery system based on the reversible deposition/stripping of aluminum at the Al negative electrode and reversible intercalation/deintercalation of chloroaluminate anions at the graphite positive electrode in a nonflammable 1-ethyl-3-methylimidazolium chloroaluminate (EMIC-AlCl 3 ) IL electrolyte (7,8). A ratio of AlCl 3 /EMIC = 1.3 by mole was used such that Al 2 Cl 7 − was present in the (acidic) electrolyte to facilitate aluminum deposition (9).…”
mentioning
confidence: 99%
“…Meanwhile,Jiaosgroup also demonstrated the rechargeability of Al-graphite cell with similar chloroaluminate electrolyte. [42] Chloroaluminate anion (AlCl 4 À1 )i ntercalated micrometer thick PG was first rapidly exfoliated at 1000 8 8C followed by ac ontrolled hydrogen evolution electrolysis treatment ( Figure 1e). [42] Chloroaluminate anion (AlCl 4 À1 )i ntercalated micrometer thick PG was first rapidly exfoliated at 1000 8 8C followed by ac ontrolled hydrogen evolution electrolysis treatment ( Figure 1e).…”
Section: Electrochemical Performances Of Al-graphene Cellsmentioning
confidence: 99%
“…[43] However,long-term cycling stability is offered by graphene with alarger crystallite size in the ab-plane and ar educed vertical dimension (c-axis). It is because of the decrease in the elastic stiffness co-efficient along the c-axis of the graphitic structure [11] c) cycle performance and d) galvanostatic charge/discharge profiles of the Al-graphene foam (GF) cell 3D graphitic foam at current rate of 4Ag À1 , [11] e) the processing and f) scanning electron microscopyi mage of the exfoliated 3D graphitic foam, [42] g) cycle performance of the exfoliated 3D graphitic Al-graphene foam (GF) cell at current rate of 12 Ag À1 . It consequently leads to premature failure of the Al-ion cell.…”
Section: Electrochemical Performances Of Al-graphene Cellsmentioning
confidence: 99%
“…10b). Wu et al [209] reported an advanced 3DGF was prepared through intercalation of chloroaluminate anion in the graphite and thermal expansion along with electrochemical hydrogen evolution in the pores of graphitic sheets occurred subsequently. The method prevented a lot of irreversible oxidation of graphite and avoided introduction of extensive oxidation-induced defects into the graphene sheets.…”
Section: Graphitic Materialsmentioning
confidence: 99%